Effect of freeze-thaw cycle aging on biochar application in DEHP contaminated Mollisols: Insights from soil properties and microbial community - Lei Wang; Wenqian Zhang; JiaXuan Yao; Zewei Qi; Yi Liu; Zhe Li; Jianhua Qu; Yunqiao Ma; Ying Zhang (Ecotoxicology and Environmental Safety)
Biochar holds significant promise for remediation of organic pollutants. However, the impact of biochar on di-(2-ethylhexyl) phthalate (DEHP)-contaminated Mollisols after freeze-thaw cycles is largely unknown, according to the seasonal traits observed at high latitudes. In this study, fresh biochar (BC) was produced from corn straw, and freeze-thaw aging biochar (FBC) was prepared by simulating winter temperatures in the Mollisol region of Northeast China using BC as a precursor. Pot experiments were conducted to evaluate the effects of freeze-thaw aging on the detoxification efficiency of biochar, the improvement of soil physical and chemical properties, and the regulation of soil microbial community structure and functional genes. The results indicated that biochar after freeze-thaw cycling significantly improved the physical and chemical properties of Mollisols compared with the control, reducing DEHP content by 99.08 % after 28 days. Metagenomic sequencing further revealed the presence of microorganisms and genetic elements potentially involved in DEHP degradation in the soil. The treatment group with freeze-thaw aging biochar exhibited higher microbial diversity and abundance, particularly in Proteobacteria, Bacteroides, and Firmicutes. Analysis of the DEHP degradation pathway via benzoic acid route revealed an increase in the abundance of degraded functional genes/enzymes (benC-xylZ, pacL, catB, pcaG, mhpE, and mhpF). The up-regulation of nitrogen fixation genes and nitrification genes (amoB, hao, narG, nifD, and vnfH) along with a 49.19 % increase in soil microbial biomass nitrogen suggested that freeze-thaw aging biochar benefited nitrogen cycling. Furthermore, the feasibility of applying biochar to high-latitude agricultural settings was validated using pakchoi (Brassica rapa L. ssp. chinensis) as a test crop. These findings suggest that the freeze-thaw aging process enhances the effectiveness of biochar in remediating DEHP-contaminated Mollisols. This study offers a novel perspective on the restoration and improvement of Mollisol productivity in high-latitude regions through biochar application.